2017
DOI: 10.18632/oncotarget.22339
|View full text |Cite
|
Sign up to set email alerts
|

C3G promotes a selective release of angiogenic factors from activated mouse platelets to regulate angiogenesis and tumor metastasis

Abstract: Previous observations indicated that C3G (RAPGEF1) promotes α-granule release, evidenced by the increase in P-selectin exposure on the platelet surface following its activation. The goal of the present study is to further characterize the potential function of C3G as a modulator of the platelet releasate and its implication in the regulation of angiogenesis.Proteomic analysis revealed a decreased secretion of anti-angiogenic factors from activated transgenic C3G and C3G∆Cat platelets. Accordingly, the secretom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 57 publications
6
40
0
Order By: Relevance
“…The production of megakaryocytes from adult HSC of bone marrow (BM), cultured in the presence of TPO and a cocktail of cytokines, is an ex vivo model commonly used to study the mechanisms involved in the expansion and differentiation of megakaryocytic progenitors. To study, in this ex vivo model, the participation of C3G in megakaryopoiesis, we have used two lineages of transgenic mice for C3G (2C1 and 6A6) and one for C3GΔCat (8A3 lineage), where the transgenes are expressed under the PF4 gene promoter [21, 23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of megakaryocytes from adult HSC of bone marrow (BM), cultured in the presence of TPO and a cocktail of cytokines, is an ex vivo model commonly used to study the mechanisms involved in the expansion and differentiation of megakaryocytic progenitors. To study, in this ex vivo model, the participation of C3G in megakaryopoiesis, we have used two lineages of transgenic mice for C3G (2C1 and 6A6) and one for C3GΔCat (8A3 lineage), where the transgenes are expressed under the PF4 gene promoter [21, 23].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have recently described a role of C3G in platelet secretion, mainly through GEF-independent mechanisms. Thus, transgenic expression of C3G in platelets modulates α-granule exocytosis through interaction with VAMP-7, which results in an overall proangiogenic secretome, facilitating inflammatory angiogenesis and tumor metastasis [23].…”
Section: Introductionmentioning
confidence: 99%
“…C3G expression increases in human non-small-cell lung cancer [ 38 ] and in the papillary thyroid carcinoma, C3G is also implicated [ 39 ]. In addition, transgenic expression of C3G in platelets promotes tumor angiogenesis and metastasis [ 40 ]. Finally, chronic myeloid leukemia is associated with a high expression of the p87C3G isoform [ 17 ].…”
Section: Rap and C3gmentioning
confidence: 99%
“…The transgenic mice models used in this work have been previously described. [2][3][4] The human transgenes C3G (full-length) and C3GΔCat (deletion in the catalytic region) were expressed under the control of the platelet-specific PF4 gene promoter. Transgenic C3G (tgC3G) lines 2C1 and 6A6 and transgenic C3GΔCat (tgC3GΔCat) line 8A3 were used.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…Transgenic expression of C3G in platelets stimulates (i) megakaryocytic differentiation and proplatelet formation, 2 (ii) platelet activation and aggregation, 3 and (iii) αgranule secretion and platelet angiogenesis and metastasis. 4 In addition, we have shown that C3G participates in the activation of Rap1 triggered by thrombin and PMA (phorbol 12-myristate 13acetate) through the PKC pathway. 3 Other investigations have demonstrated the formation of a ternary VASP/CrkL/C3G complex that activates platelet Rap1b.…”
Section: Introductionmentioning
confidence: 95%